FOR SHALLOW GOOD IRRIGATION TECHNOLOGY INNOVATION TO INCREASE THE INCOME OF CORN FARMERS ON RAINFED LAND IN SIGI REGENCY, CENTRAL SULAWESI - Suwitra, I Ketut; Negara, Abdi; Fattah, Abdul; Supriadi, Khojin; Udiarto, Bagus K; Khasanah, Nur; Mustakim, Mustakim; Ardjanhar, Asni (AGROLAND The Agricultural Sciences Journal (e-Journal), 2024)
The area of ​​agricultural land in Indonesia is dominated by rainfed rice fields whose limiting factors are limited water, low land productivity, and low levels of technology adoption. This research was carried out from April 2019 to August 2019. On rainfed land in Karawana Village, Dolo District, Sigi Regency, Central Sulawesi. The technology used is shallow good irrigation pumping. This study aims to develop maize cultivation to increase the production and productivity of strategic commodities with shallow good pumping technology. The results showed that: (a) One technology package through the development of a shallow well irrigation system with pumping which refers to the availability of water and plant needs optimally by using water gun technology. (b) The establishment of an innovative design for rainfed dry land food crops with the production component of tile products with 9.4 tons Lamuru, 6.8 tons/ha, Sukmaraga 6.2 tons/ha, 5.0 tons without weights /ha, R/C: Ratio: 2.16